Consumer Behaviour, Marketing Strategy, Customer Satisfaction, and Business Performance - I Ketut Kanten; Gede Sri Darma (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe purpose of this research is to examines the influence of consumer behariour on marketing strategy, customer satisfaction and business performance, the influence of marketing strategy on customer satisfaction and business performance, and the influence of customer satisfaction on business performanceThe population used in this study were guests who stayed in a Villa unit sand Hotels under the management of Alpha Hotel Management, Bali – Indonesia, with a total of 171 respondents. Data were collected by using questionnaire, where the sampling method in this study using combination of purposive and accidental sampling.Technical analysis used is a quantitative analysis with SEM (Structural Equation Model) analysis method using AMOS. The results showed that consumer behavior has a positive and significant impacts on marketing strategy and customer satisfaction, positively insignificant impact on business performance. Marketing strategy has a positive significant impacts on customer satisfaction, but negative insignificants impact on business performance. While customer satisfaction has a positive and significant impact on business performance. Research also figure out that marketing strategy and customer satisfaction strengthen the impact of consumer behavior on business performance. Reseracher conclude that in order to gain better business performance, the marketer of a company has to combining all variables (Consumer Behaviour, Marketing Strategy, and Customer Satisfaction) rather than just focusing their efforts only on Marketing Strategy, where ensuring the highest level of Customer Satisfaction should become the most essential efforts to gain the highest Business Performance. Researcher suggest that future study be carried out using the same methodology but encompassing bigger areas of population and sampling, and uses more variables and indicators.